Multicomponent exercise program effects on fitness and cognitive function of elderlies with mild cognitive impairment: Involvement of oxidative stress and BDNF - Rondão, Catarina Alexandra de Melo; Mota, Maria Paula; Oliveira, Maria Manuel; Peixoto, Francisco; Esteves, Dulce (Frontiers in Aging Neuroscience, 2022)
Regular exercise has been shown to be one of the most important lifestyle influences on improving functional performance, decreasing morbidity and all-cause mortality among older people. However, and although there is some evidence of the effects of aerobic training on oxidative stress, there is little information on the effects of combined exercise training (dual-task training, combination of exercise with cognitive stimulation) on oxidative stress. With this in mind, the aim of this study was to verify the Effects of multicomponent exercise programs on physical fitness and cognitive function in the elderly with mild cognitive impairment: involvement of oxidative stress and BDNF. At baseline, 37 elderly nursing home residents with mild cognitive impairment were divided into two groups: the control group (CG, n = 12: 81.8 years), and the experimental group (EG, n = 25: 83.2 years). These elderly people integrated a multicomponent exercise training program for 24 weeks, 2 sessions of 50 to 60 min per week. Physical assessments (weight, height, body mass index), health and functional parameters (fitness tests: Chair stand, Arm Curls, Chair sit-&-Reach, 8-Ft Up-&-Go Back Scratch, Six min walking, Feet together, Full Tandem, Semi Tandem, Full Tandem) lipid profile ( Total Cholesterol, HDL, LDL, and Triglycerides) and measures of lipid peroxidation damage thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC) and Brain-Derived Neurotrophic Factor (BDNF) were performed analyses before and after the 24 weeks of multi-component exercise intervention. The results showed an overall improvement in physical and functional performance. Regarding biochemical measures, exercise training-induced a significant decrease in oxidative damage. The results indicate that combined exercise training induces benefits in functional capacity and reduces oxidative stress damage.